Esperienza, fede e ragione nel Nietzsche ‘religioso’ - Messinese, Leonardo (B@belonline, 2021)
The intent of this reflection is to highlight some key words and some main lines of Massimo de Angelis’ book. In such a way it is possible to justify the interpretative thesis that guides this short essay, which underlines how De Angelis, through a personal and passionate reading of Nietzsche’s works and by reviewing the different phases of his philosophical production, comes to offer a presentation of Nietzsche’s thought in a ‘religious’ key. In the conclusion, I synthetically discuss the thesis accepted also by De Angelis, which is prevalent in contemporary thought, according to which it would not be possible to transcend experience on the basis of ‘pure reason’.